Answer:
327 Seconds
Step-by-step explanation:
7/.75=28/3
28/3 X 35 = 327 Seconds
Since the constant has been moved to the left side, you can move on to the next step which is adding (b/2)² to both sides of the equation.
h² + 14h + (14/2)² = -31 + (14/2)²
Simplify the parenthesis and exponent.
h² + 14h + 7² = -31 + 7²
h² + 14h + 49 = -31 + 49
h² + 14h + 49 = 18
Factor the expression of the left.
(h + 7)(h + 7) = 18
Take the square root of both sides.
√(h + 7)(h + 7) = ± √9 • 2
(h + 7) = ± 3√2
h + 7 = ± 3√2
Subtract 7 from both sides.
You solutions are:
h = -7 + 3√2 → -2.7573 → -2.76
h = -7 - 3√2 → -11.2426 → -11.24
1] y - 3x = -8
[2] y + 9x = 4
-3x + y = -8 9x + y = 4
Solve equation [2] for the variable y
[2] y = -9x + 4
// Plug this in for variable y in equation [1]
[1] (-9x+4) - 3x = -8
[1] - 12x = -12
// Solve equation [1] for the variable x
[1] 12x = 12
[1] x = 1
// By now we know this much :
y = -9x+4
x = 1
// Use the x value to solve for y
y = -9(1)+4 = -5
{y,x} = {-5,1}
Answer:
The answer is C
Step-by-step explanation: